Ina, Bakit Naaga?: A Lived Experiences of Postpartum Mothers with Preterm Infant - Pascual, Fiona Alexandra P.; Navarro, Andrea Jasmin B.; Mendoza, Justine J.; Chioco, Eriza Mhae P.; Madayag, Gimena Anne Paula G.; Mangulabnan, Jemmie A.; Alday, Cecille L. (Proceedings Series on Health & Medical Sciences, 2025)
This qualitative study delves into the lived experiences of mothers with preterm infants, aiming to shed light on their challenges, coping strategies, and insights for future mothers. The significance of this research lies in its potential to offer valuable support and guidance to mothers navigating the complexities of caring for preterm infants. This study utilized a phenomenological research design, engaging a specific group of participants, consisting of 15 mothers with preterm infants, within the scope of Nueva Ecija, Philippines. The inclusion was based on the following criteria: Mothers who have given birth to a preterm infant (born before 37 weeks of gestation), who have delivered preterm infants within the past 6 months, and who are residing in Nueva Ecija. The exclusion requirements were also: Pregnancies that ended in stillbirth and postpartum mothers with preterm infants who are still admitted to the Neonatal Intensive Care Unit (NICU). Additionally, snowball sampling was used with selected participants, it also employed a semi-structured interview guide, responding to predetermined open-ended questions. From the shared narratives, a multitude of challenges faced by mothers of preterm infants have been uncovered, these vividly depict the emotional challenges experienced by mothers. Furthermore, they highlight the significance of staying strong, embracing challenges, nurturing sincere relationships, and trusting one's faith. Postpartum mothers face a spectrum of emotions, including joy, sadness, anxiety, depression, fear, and self-doubt, compounded by the unpredictability of their infants' health and development. Coping strategies include reliance on support systems, belief, self-love, engagement in diverse activities, and virtual communities.